Great leap forward famine exposure and urban-rural migration convolute the modern prevalence of diabetes in China - Dian Luo; Wan-chin Kuo (BMC, 2024)
Abstract Background Although evidence from birth cohort analysis has indicated the metabolic risk of early-life exposure to the Great Leap Forward Famine (GLFF) in China, three confounding effects, including the exposure windows, aging, and geographical variations in famine severity, have been brought to debates for a decade. This study aimed to address these confounding effects and extensively examine how GLFF exposure is associated with diabetes risk in mid-to-late life and its interaction with urban-rural migration. Methods Data from the China Health and Retirement Longitudinal Study (CHARLS) were analyzed with age-stratification and stepped wedge approaches. Weighted prevalence and multivariable logistic regression were used to investigate the effects of GLFF exposure and urban-rural migration on mid-to-late life diabetes risk and the interaction between GLFF exposure and urban-rural migration. Birth provinces were controlled as a fixed effect to account for variations in famine severity across provinces. Results Compared to those who were never exposed to GLFF, fetal GLFF exposure was associated with a higher risk of adult-onset diabetes after controlling for provinces, demographics, and health statuses. Yet, after adding the proxy of childhood growth environments into the model, fetal exposure to GLFF was not significantly associated with adult-onset diabetes risk (OR = 1.22, p = 0.10), compared to those who were never exposed to GLFF. Across the three age-stratification groups, static urban residents, in general, had a higher risk of diabetes compared to static rural residents. Interaction effects between GLFF exposure and urban-rural migration were insignificant across all three age-stratification groups. Conclusion Fetal exposure to GLFF might have a traceable effect on adult-onset diabetes risk. Yet, the growth environment and urban lifestyle outweigh and further confound the impact of GLFF exposure on adult-onset diabetes risk.